Improved test scores, attitudes, and behaviors in America's schools : supervisors' success stories - Dunn, Rita Stafford, 1930-; DeBello, Thomas C. (Bergin & Garvey, 1999)
A study of the practical experiences of more than 30 school supervisors throughout the USA. Representing a variety of urban and suburban locations, each one provides insights into how they obtained significantly higher standardised achievement test scores for his or her student populations.